An Analysis of the AskMSR Question-Answering System - Brill, E.; Dumais, S.; Banko, M.; Brill, Eric; Banko, Michele; Dumais, Susan (Proceedings of EMNLP 2002, 2002)
We describe the architecture of the AskMSR question answering system and systematically evaluate contributions of different system components to accuracy. The system differs from most question answering systems in its dependency on data redundancy rather than sophisticated linguistic analyses of either questions or candidate answers. Because a wrong answer is often worse than no answer, we also explore strategies for predicting when the question answering system is likely to give an incorrect answer.